(untitled) (Journal of Hama University, 2020)
The goal of this study was to study some factors affecting the production costs and the economic return of the non-irrigated Cumin crop in Al Hassakeh governorate. A sample of the farmers was selected in the random sample method of the administrative districts of Al-Hasakah governorate, which is 278 farmers. Economic analysis was used to estimate the production costs, the economic yield of the non-irrigated Cumin crop during the agricultural season 2016/2017 and the analysis of the effect of some independent factors. The results of the analysis showed that the total costs of production of non-irrigated Cumin reach an averaged 250.699 thousand SP / ha and the economic return was about 560.659 thousand SP / ha. Economic efficiency was 2.24. This indicates a high profitability for the production of non-irrigated Cumin in the study area. And the factors affecting production costs are the same that affected the economic return. The most important years of experience with the farms, where the increase of years of experience one year, led to a decrease in production costs by 4240 SP / ha, and increase economic return by 3659 SP / ha. This research shows to The importance of the cumin crop, which contributes to securing profitable economic returns for farmers as well as the possibility of planting them in arid and marginal areas.